Bathyraja scaphiops, Cuphead Skate - Pollom, R. (2020)
The Cuphead Skate (Bathyraja scaphiops) is a medium-sized (to 117 cm total length) skate that occurs in the Southwest Atlantic from off Rio Grande do Sul, Brazil to Tierra del Fuego, Argentina and the Falkland Islands (Malvinas). It inhabits continental and insular shelves and slopes at depths of 30?925 m. It is targeted or captured as utilized bycatch in demersal trawl fisheries, including the southern Brazil otter trawl fishery, the Patagonian scallop and hake fisheries, and the Falkland Islands (Malvinas) targeted multi-species skate fishery. At the northern extent of its range in southern Brazil, it is captured in the otter trawl fishery which is intense; reductions in the population are suspected there but there are no data. In the Argentina-Uruguay Common Fishing Zone (AUCFZ), this species was captured frequently in commercial trawls between 1984 and 2009. On the shelf edge off Argentina between Buenos Aires and northern Santa Cruz, this species was present in 9% of research trawls in the area trawled by the Patagonian scallop fishery in 2010. In the Falkland Islands (Malvinas), this species made up an average of 3.5% of the catch in the multi-species skate fishery between 1993 and 2013, with no clear trend in catch-per-unit-effort over that time frame. Overall, although this species is subjected to substantial fishing pressure, it has remained common in catches and it may have refuge over rough substrates that are untrawlable. Although fisheries are likely leading to some reduction in population size, the level is not suspected to approach the thresholds for a threatened assessment. Therefore, the Cuphead Skate is assessed as Least Concern.